Discourse organization of want ads in Philippine English and Qatari English newspapers - Gaerlan, Marianne Jennifer M. (2008)
Contrastive rhetoric research is beginning to consider the variations in native - speaker varieties of English as well as non-native or nativized varieties. In this study, want ads in Philippine English and Qatari English newspapers were compared to see how writers of these ads use English to accomplish the ad?s objectives and at the same time adhere to the discourse community?s conventions. A modified version of Bhatia?s (1993) framework which he utilized in his analysis of job application and sales promotion letters was used to examine the structure of and moves in the want ads in the present study. Results reveal that Qatari writers of want ads tend to be more conventional in terms of structure and tend to give out less information as evidenced by the fact that fewer moves were found in their ads. On the other hand, Filipino writers of want ads also tend to be conventional in terms of structure but provided more information in the ads as evidenced by the presence of more moves. Possible reasons for the differences are discussed.
Includes bibliographical references (pages 53-54).